Electrophysiological Correlates of Empathy - Tatalović Vorkapić, Sanja (Array, 2011)
This study focused on examining whether there were any electrophysiological correlates of empathy, by analyzing the relationship between empathy and latencies/amplitudes of evoked potentials (N1, P2, N2, P3 & Sw). A sample consisted of N=54 female psychology students, within the age range 19-23 years, and all right-handers. Evoked potentials were measured by using the standard visual oddball paradigm in two trials with two occipital and two parietal electrodes. Empathy was measured by EPQ-IVE. Correlation analysis showed a significant negative correlation between empathy and N2-amplitude in the first trial at one parietal electrode (r=-.36, p<.01). More empathetic students showed lower extraction of stimuli characteristics and target selection during task, probably due to fronto-central distribution of N2-component. This kind of distribution has been usually registered in participants experiencing empathy, as it was expected. Also, lack of other significant correlations could be explained by the very simple and neutral task that has been used.